PKM Peningkatan Kemampuan E-Marketing Kepada Pelaku UMKM Arak Bali di Desa Datah, Karangasem - I Made Astu Mahayana; Gde Deny Larasdiputra; Ni Luh Putri Jelitayanti; I Gede Deva Pratama; Ida Ayu Ulan Antika Putri; I Putu Arya Loka Aditya Gautama (Postgraduated Community Service Journal, 2023)
Balinese Arak is an intangible cultural heritage that has been established by the Ministry of Education and Culture of the Republic of Indonesia. The Community Partnership Program (PKM) in Datah Village, Karangasem Regency aims to help partners in the economic sector, namely the Bali Arak UMKM. There are 2,285 Balinese wine craftsmen in Karangasem Regency. The increasing number of Balinese wine SMEs, Balinese wine craftsmen are demanded to be active and creative in promoting and making the right marketing strategy. For this reason, the PKM team targeted Balinese wine SMEs in Banjar Lebah, Datah Karangasem Village. There are two problems found, namely the lack of public awareness and knowledge in product marketing through the use of social media and the less optimal use of attractive, informative and persuasive advertising language in uploaded content. The implementation method used is to collect partners' knowledge about e-commerce platforms and media facilities used, socialize the benefits of social media, and use interesting language in e-commerce, provide training and monitor partner business developments online. The PKM team is assisted by students in providing assistance regarding designs and attractive language choices using online methods. The outputs of the PKM implementation are in the form of articles published in PCS journals, publications in counter mass media and publications on Youtube, and increased understanding of partners in the use of good advertising language in creating promotional content and understanding e-marketing sales strategies.